Social movements an introduction - Della Porta, Donatella 1956-; Diani, Mario 1957- (Wiley-Blackwell, 2020)
"Now in its third edition, Social Movements is the market-leading introductory text on collective action in contemporary society. The text draws from theory-driven, systematic empirical research from across the social sciences to address central questions and concepts in the field. Sophisticated yet reader-friendly chapters offer critical analyses of relevant literature whilst exploring important issues and debates. The global political landscape has undergone significant changes in the years since this book's initial publication, such as the spread of online protests, the resurgence of nationalist and right-wing activity, global revolts, and increased social and economic polarization. This thoroughly updated edition offers fresh discussions of recent social movements against austerity from around the world, new empirical examples, references to recent episodes of contention, an expanded comparative approach to social movement theory in the scientific literature, and more. Presents an empirical and engaging exploration of contemporary social movements. Discusses topics such as organizing within social movements, eventful protests, political opportunities, symbolism and identity in collective action, and social change. Highlights how core mechanisms of collective action operate in different movements, past and present. Provides a conceptual methodology useful for social science students and researchers alike. Highlights how core mechanisms of collective action operate in different movements in the past and present"--
Keywords: Soziale Bewegung; Politische Bewegung; Soziologie; Kollektive Handlung; Social movements